Pet sheet and tray formed by using the sheet
A three-layer PET sheet with polycarbonate and A-PET layers addresses the low heat deformation and rapid crystallization issues of A-PET trays, ensuring stability and transparency in vacuum molding, particularly for transporting electronic components.
Patent Information
- Application Number
- JP2023119268
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
A-PET trays used for vacuum molding have low moisture-resistant heat deformation temperature, leading to potential deformation during transportation, especially in high-temperature environments, and lack stability in manufacturing conditions due to rapid crystallization, affecting transparency and workability.
A three-layer PET sheet structure with a polycarbonate layer on either side and A-PET as the middle layer, maintaining transparency and improving heat resistance by delaying crystallization, using specific ratios and properties of A-PET and polycarbonate.
The PET sheet maintains transparency and achieves a high moisture-resistant heat deformation temperature, enhancing workability and preventing deformation during transportation, while maintaining the rigidity and visibility of stored parts.
Smart Images

Figure 2025016166000001 
Figure 2025016166000002 
Figure 2025016166000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a PET sheet made of A-PET, which is easily applicable to vacuum forming, pressure forming, or press forming, and therefore has excellent workability, and the obtained tray product has an improved resistance to moist heat distortion temperature while maintaining the transparency of the A-PET material, and to a tray made of said sheet. [Background technology]
[0002] PET resin is used for various purposes in the form of fibers, sheets, molded products, etc., and the amount used is extremely large. Depending on the purpose and method of use, the PET resin used as a material for products may be used as it is as an amorphous resin (A-PET), but it may be subjected to various treatments, such as crystallization by heating or stretching to improve heat resistance, and may have a wide variety of forms (characteristics). Among these, the present invention is particularly directed to PET sheets used as a forming raw material (material) in the field of producing trays by a processing method of vacuum molding (used in this specification to include air pressure molding and press molding). The PET resin used in the sheets for vacuum molding is an amorphous resin (A-PET) for molding reasons.
[0003] A-PET is generally transparent, has excellent rigidity, and is scratch-resistant, making it suitable as a material for trays used to transport various items. It is particularly widely used for transporting electronic and electrical parts between processes within factories, and between factories both domestically and overseas. The reasons for its widespread use include the fact that the transparent material allows for easy visual confirmation of delivered parts, and the high rigidity of A-PET makes it difficult for the tray to deform, preventing damage to parts inside the tray due to external forces. In addition, trays made of A-PET have the advantage of having low surface friction resistance, making them excellent at preventing damage to parts due to sliding during transportation.
[0004] On the other hand, the biggest drawback of A-PET tray products is their low heat distortion temperature, but a particularly big problem is that their heat distortion temperature decreases due to moisture absorption (i.e., moisture-heat distortion temperature). It is widely known in the market that moisture absorption reduces the heat resistance of products made of A-PET. For example, Patent Document 1 describes a phenomenon in which a molded bottle stored for a long time cannot withstand the filling temperature that it could withstand immediately after molding. Patent Document 1 also discloses that when hot water of the same temperature is poured into a simultaneously molded bottle that has been left in a room for a long time, deformation due to thermal shrinkage is observed on the lower side and bottom of the body, while the bottle after drying does not undergo thermal deformation as in the case immediately after molding, and states that it is effective to configure it in this way. That is, Patent Document 1 proposes preventing the deterioration of heat resistance of polyester resin heat-resistant containers due to moisture absorption by drying them before use.
[0005] The above phenomenon cannot be explained by mere hydrolysis due to moisture absorption, because the melt mass flow rate of A-PET resin cannot be measured accurately unless the drying conditions of the sample are strict, and the normal value is obtained when the same sample is dried again. For example, plasticization due to moisture is also considered, and the reason for the above phenomenon is not clear at present. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-39105 Summary of the Invention [Problem to be solved by the invention]
[0007] Another technical issue with A-PET is that it crystallizes quickly due to heat, and because of this property, stable vacuum molding conditions for A-PET materials are difficult. Here, the main structure of A-PET is a high molecular weight polyester produced by condensation polymerization of terephthalic acid and ethylene glycol. Although the molecular weight distribution is relatively wide and contains many parts in the low molecular weight region, it has a simple structure. And because of this simple structure, A-PET is very easy to crystallize, and it easily changes to an opaque, high melting point phase due to heat, stretching, solvents, etc. On the other hand, this property of easy crystallization is an advantage when using A-PET as a material, but it also causes disadvantages as explained below. For example, during vacuum molding, a very limited temperature range and processing time are required for the work. In other words, if the temperature range considered to be suitable is exceeded or the heating time is longer than necessary, crystallization progresses in a short time, accompanied by whitening, and accurate transfer of the mold dimensions cannot be obtained. For this reason, when A-PET sheets are used as the material for vacuum molding, the optimum molding conditions are currently determined by craftsmanship based on experience, taking into account the thickness of the sheet, the complexity of the mold, as well as the characteristics of the machine to be used, etc. When A-PET is used as the material in this way, improving workability during vacuum molding is an issue, along with improving the aforementioned resistance to moist heat distortion temperature.
[0008] According to the study by the inventors, trays using A-PET as a material have the following problems. First, the glass transition point of A-PET in a dry state is around 70°C, while the temperature at which crystallization clearly progresses is 120°C or higher. Therefore, if an A-PET tray containing various parts is placed in a temperature range between these temperatures, it will soften and deform, which may cause an accident that damages the parts. In particular, electronic parts are expensive and have extremely fine circuit structures, so that in the event of an accident, huge damage will occur. On the other hand, trays crystallized under special conditions have an extremely high softening temperature, making them possible to be used in a high-temperature atmosphere. However, it is difficult to establish stable manufacturing conditions for the above-mentioned crystallized trays, and further, the obtained trays are generally whitened and opaque, and the good transparency of A-PET is lost.
[0009] When using the above-mentioned A-PET as a material, in order to avoid the contradiction that amorphous A-PET has a low softening temperature and must be crystallized to increase the softening temperature, other resins are used as the tray material when it is applied to products intended for use at relatively high temperatures. For example, ABS, high impact polystyrene (HIPS), and polypropylene (PP) are used to prevent damage caused by temperature during transportation of electronic parts. However, ABS and HIPS are opaque, making it difficult to visually check the delivery status of the parts inside the tray, and when a tray is molded with PP, warping is likely to occur after molding, which is another problem that often requires forced correction after molding.
[0010] As can be understood from the above, the market is eagerly awaiting the development of a transparent tray made of A-PET that has improved resistance to heat and moisture distortion temperature and allows the parts stored inside to be seen. In addition, in recent years, with the progress of global warming due to environmental changes, there is a tendency for A-PET trays to become deformed frequently during transportation in a sealed state. This is particularly problematic during land transportation by truck and sea transportation in containers. Due to the effects of global warming, for example, it has been reported that the temperature of the ceiling of containers on sea transportation routes and in container yards can reach 50 to 60 degrees Celsius (see http: / / www.monohakobi.com / ja / wp-content / uploads / 2011 / 12 / 20111214_MTF4_kondo.pdf), and the environment in which A-PET trays are used is becoming harsher.
[0011] Therefore, the main object of the present invention is to develop a technology that can stably provide trays that have an improved moist heat distortion temperature, which is a drawback when A-PET is used as a tray material, and that maintain the transparency that allows the parts stored therein to be visually recognized. Furthermore, the object of the present invention is to improve the workability during vacuum molding by lengthening the time until the start of crystallization accompanied by whitening that occurs during the vacuum molding process (hereinafter referred to as delay time) in addition to the above-mentioned effects, by using a preferred embodiment of the present invention. That is, the final object of the present invention to make the technology more useful is to provide a PET sheet and a tray using the sheet that, while using A-PET as a material, is particularly easy to apply to vacuum molding, has excellent workability during molding, and the tray product obtained using the A-PET material is useful in that it maintains the transparency of the A-PET material and exhibits a high moist heat distortion temperature. [Means for solving the problem]
[0012] The above object can be achieved by the present invention described below. That is, the present invention is achieved by the PET sheet of the present invention described below. [1] A PET sheet used in vacuum molding, pressure molding, or press molding, characterized in that it is a laminate having a three-layer structure in which the upper layer is a resin layer containing polycarbonate, the middle layer is a resin layer mainly composed of A-PET (amorphous PET), and the lower layer is a resin layer containing polycarbonate.
[0013] Preferred embodiments of the PET sheet of the present invention are as follows. [2] The PET sheet according to the above [1], wherein the intermediate layer contains polycarbonate and has a volume ratio of A-PET / polycarbonate of 98 / 2 to 70 / 30. [3] The PET sheet according to the above [1] or [2], wherein the polycarbonate constituting the upper layer and the polycarbonate constituting the lower layer have the same thickness. [4] The PET sheet according to any one of the above [1] to [3], wherein the ratio of the total thickness of the upper layer and the lower layer to the thickness of the intermediate layer is 10 / 90 to 30 / 70. [5] The PET sheet according to any one of the above [1] to [4], wherein the thickness of the laminate having a three-layer structure is 300 μm to 1200 μm. [6] The PET sheet according to any one of the above [1] to [5], wherein the polycarbonate has a melt mass-flow rate (ISO1133) at 300°C in the range of 3 to 30 (g / 10 min) and a deflection temperature measured by JIS7191 B method of 100°C or higher and 150°C or lower. [7] The PET sheet according to any one of the above [1] to [6], wherein the A-PET is a reaction product obtained by using a homopolymer or a modified copolymer as a raw material, and the IV value measured in a 1 / 1 phenol / 1,1,2,2-tetrachloroethane solvent is 0.5 to 1.3.
[0014] As another embodiment, the present invention provides the following tray using the PET sheet of the present invention. [8] A tray formed by vacuum forming, pressure forming, or press forming, characterized in that the raw material for the tray is the PET sheet described in any one of [1] to [7] above. Effect of the Invention
[0015] According to the present invention, it is possible to provide a technique for improving the moist heat distortion temperature, which is a drawback when A-PET is used as a tray material, and to stably provide a tray that maintains transparency that allows the parts stored therein to be visually recognized. That is, according to the present invention, it is possible to provide a technique for providing a PET sheet and a tray using the sheet, which uses A-PET as a material, is particularly easy to apply to vacuum molding, and the tray product obtained using the A-PET material maintains the transparency of the A-PET material and exhibits a high moist heat distortion temperature. In addition, according to a preferred embodiment of the present invention, the time until the start of crystallization accompanied by whitening that occurs during the vacuum molding process is extended (delay time), thereby achieving improvement in workability during vacuum molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As a result of intensive research aimed at solving the above technical problems, the present inventors discovered that the technical problems of the present invention could be solved by a PET sheet having the configuration of the present invention, and thus arrived at the present invention. That is, the PET sheet of the present invention is a PET sheet used for vacuum molding, pressure molding, or press molding, and is characterized in that it is a laminate having a three-layer structure in which the upper layer is a resin layer containing polycarbonate, the middle layer is a resin layer mainly composed of A-PET (amorphous PET), and the lower layer is a resin layer containing polycarbonate.
[0017] The following describes the points that the inventors have considered in solving the technical problems of the present invention described above. First, when improving the wet heat distortion temperature while maintaining transparency, it is difficult to use A-PET alone, and it is considered that sharing (combination) with other resins or promoting crystallization is effective. When using A-PET with other resins, it is required to use an engineering plastic that is miscible with A-PET resin and has a high heat distortion temperature. From the viewpoint of compatibility and miscibility, polyester resin, which is a resin with a raw material composition close to that of A-PET resin, is preferable. For example, although polybutylene terephthalate (PBT) does not have a high glass transition point, blending it with A-PET has the effect of accelerating its crystallization, making it easier to control the crystallization. In addition, blending A-PET with polynaphthalene terephthalate (PEN) can increase the glass transition point and improve the heat resistance temperature.
[0018] However, these polyesters are extremely expensive, and in addition, since an ester exchange reaction occurs during the melt-kneading process, it is difficult to stably obtain certain characteristics. Therefore, it is difficult to say that any of these polyesters is suitable for the objects and means of the present invention.
[0019] In contrast, polycarbonate is an engineering plastic that has a high heat distortion temperature and is compatible with A-PET resin. Although A-PET and polycarbonate (hereinafter abbreviated as PC) are highly compatible, it is known that the glass transition temperature of the mixture shows two peaks (see Polymer Literature Collection Vol. 49 No. 4, pp. 327-334 (1992), Makromol. Chem. Rapid Commun. 7, 5-259 (1986)). Various prior art using PET and PC are explained below.
[0020] There are various theories on the compatibility of A-PET / PC, such as a theory of complete compatibility, a theory that denies it, or even a theory that they are integrated by an ester exchange reaction under melting and kneading conditions during blending. In any case, it has been confirmed that in practice, the heat resistance is improved by blending A-PET / PC, and this point can also be understood from the description of JP-A-9-176465, which discloses an invention related to a heat-resistant container using a transparent polyester / polycarbonate composition obtained by melt kneading. Due to the above-mentioned characteristics, as listed below, many patent applications using A-PET and PC have been filed and various disclosures have been made. For example, the above-mentioned publication proposes that a PC / PET composition with a single glass transition point can be obtained by melt kneading PC and PET in the presence of an ester exchange catalyst, and thus a transparent heat-resistant container in which crystallization is suppressed can be obtained even when heat-treated at a temperature above the glass transition temperature.
[0021] According to the formulation of the examples of this invention, it is said that good results are obtained when the transesterification catalyst is sodium hydroxide, a strong alkali, but according to the study by the present inventors, this catalyst strongly decomposes polycarbonate and is not preferable. In any case, the method in this prior art is mainly composed of generating a polymer with a new structure by transesterification of two resin materials, PC and A-PET, and is not a method of solving the technical problems when A-PET is used as a material by combining PC material and A-PET material as they are.
[0022] Furthermore, in order to obtain a composition with excellent heat resistance (high glass transition temperature) using the above technology, the PC / PET ratio must be 60% or more, with an overwhelmingly high amount of PC blended in. For this reason, the above conventional technology has a large practical problem of resulting in an expensive material composition, which affects the final product cost.
[0023] Furthermore, JP-A-10-219122 proposes a thermoplastic resin sheet having a 60° gloss (glossiness) of 20 or less and a pencil hardness of 2H or more, the main components of which are a crystalline thermoplastic resin such as 40 to 80% by weight of polyethylene terephthalate, a non-crystalline thermoplastic resin such as polycarbonate, and an inorganic filler containing 20% by weight or more of silicon oxide. The above technology relates to a polymer alloy in which the non-crystalline thermoplastic resin contains a crystalline thermoplastic resin, and although polyethylene terephthalate is mentioned as the crystalline thermoplastic resin, there is no mention of A-PET (amorphous resin), nor of the transparency and wet heat distortion temperature resistance of the thermoplastic resin sheet, which are the subject of the present invention.
[0024] In addition, JP 2009-196153 A proposes a laminated sheet having a coating layer mainly composed of an acrylic resin (B) on one side of a base layer mainly composed of a polycarbonate-based resin composition (A) consisting of a polymer alloy of an aromatic polycarbonate (A1) and another resin (A2), and claims that this configuration produces a sheet that can be deep-drawn. It also discloses that an aromatic polyester is used as the other resin (A2) constituting the polymer alloy.
[0025] In addition, JP 2012-077240 A discloses a melt tension improver containing a reaction product of an aromatic polycarbonate resin, polyethylene terephthalate (polyethylene terephthalate) in which a polycondensation catalyst has been deactivated, and an olefin polymer having a functional group reactive with PC. It is said that a container with improved warpage can be produced by extrusion molding a polycarbonate-polyester composite resin composition using this, which has excellent extrusion moldability and the like.
[0026] In addition, JP-A-9-12847 discloses a filler-reinforced aromatic polycarbonate resin composition based on a resin composition consisting of a PC component and a PET component, which has a good surface appearance when molded into a molded article, and is excellent in mechanical properties such as chemical resistance, impact strength, and rigidity. In addition, JP-A-2009-1620 discloses that a thermoplastic resin composition having a good balance of various resin properties such as flowability, heat resistance, impact resistance, residence heat stability, chemical resistance, and moist heat resistance can be obtained by adding a specific organic phosphate ester compound to a polymer alloy of an aromatic polycarbonate resin and a polyethylene terephthalate resin produced using an antimony compound as a polymerization catalyst. In addition, JP 2010-77196 A describes a polycarbonate resin composition for profile extrusion molding, which contains a polymer of a monomer selected from the group consisting of an aromatic polycarbonate resin, a crystalline polyester resin, a thermoplastic elastomer, and a monoolefin compound and a diolefin compound, and which has a functional group that reacts with polycarbonate.
[0027] As described above, all of the technologies described in the prior art utilize PC and PET, but they are related to component materials that aim to improve fluidity, chemical resistance, and heat resistance by mixing or homogenizing each component of PC and PET, and have a completely different basic structure from the PET sheet of the present invention, which is a laminate having a three-layer structure of PC / A-PET / PC. This difference in structure is due to the purpose of the present invention being to develop a technology that is not described in the prior art at all, which uses A-PET as a material, but can be applied when making trays and the like by vacuum molding using PET sheets, has excellent workability, and the tray product obtained by vacuum molding using the A-PET material maintains the transparency of the A-PET material and is useful in showing a high moist heat distortion temperature.
[0028] According to the study by the present inventors, even if one of the objectives of the present invention, easiness of application of vacuum molding, is aside, it is expected that in order to obtain a composition with a high heat distortion temperature resistance using a PC / PET mixed system, at least the blending ratio of polycarbonate must be set to a large value. According to the above-mentioned document [Polymer Literature Collection Vol. 49 No. 4, pp. 327-334 (1992)], for example, in order to increase the heat distortion temperature resistance to 80-90°C, the A-PET / PC ratio requires 30-40% or more of PC. For example, in the field of general-purpose products such as carrier trays, a high ratio of PC components in the material of the general-purpose product means that the product becomes expensive, which places a large economic burden on the general-purpose product and becomes a major practical problem. The practical problem in this prior art means that it is not suitable as a technology for application to general-purpose products.
[0029] In view of the above-mentioned current situation, the present inventors have come to recognize the importance of developing a technology that can provide a PET sheet with excellent properties as a material for vacuum molding, which is easy to apply to vacuum molding and which allows the manufactured general-purpose products such as trays to have a high heat distortion temperature and maintain the transparency of A-PET, in an economical manner, rather than relying on the conventional technique of mixing or homogenizing the components of PC and PET, and as a result, have arrived at the present invention. Specifically, the present inventors have found that the object of the present invention can be achieved by providing a PET sheet having a three-layer structure in which an intermediate layer is a resin layer mainly composed of A-PET, and upper and lower resin layers containing polycarbonate (PC) are provided on both sides of the intermediate layer.
[0030] Furthermore, the present inventors have found that, as a more preferable configuration, the intermediate layer mainly composed of A-PET contains polycarbonate and has a volume ratio of A-PET / PC=98 / 2 to 70 / 30. That is, by configuring in this way, the time (delay time) until the start of crystallization accompanied by whitening during the vacuum molding process can be extended, and this makes it possible to realize improvement in workability during vacuum molding. Furthermore, it has been found that it is preferable that the upper and lower layers constituting the three-layer structure are resin layers containing substantially the same PC and substantially the same thickness of PC. And, it has been found that it is preferable that the three-layer structure is configured such that the ratio of the total thickness of the upper and lower layers containing PC to the thickness of the intermediate layer mainly composed of A-PET is 10 / 90 to 30 / 70. Furthermore, it has been found that the thickness of the laminate having a three-layer structure is preferably 300 μm to 1200 μm, depending on the application.
[0031] Furthermore, according to the study by the present inventors, it is preferable to use a polycarbonate constituting the present invention that has a melt mass flow rate (ISO1133) value at 300°C in the range of 3 to 30 (g / 10 min) and a deflection temperature measured by JIS7191 B method of 100°C or more and 150°C or less. In addition, it is preferable to use a reaction product made from a homopolymer or modified copolymer as a raw material, whose IV value measured using a 1 / 1 phenol / 1,1,2,2 tetrachloroethane solvent is within the range of 0.5 to 1.3, as the A-PET constituting the intermediate layer constituting the present invention. The IV value is a value measured in accordance with the measurement method of JIS 7367-5.
[0032] <Heat distortion temperature> With regard to the "improvement of wet heat distortion temperature" that is the subject of the present invention, the inventors will explain the term "heat distortion temperature" used in the present invention, and the official "glass transition temperature" (JIS K 7121-1987) and "deflection temperature" (ASTM D648-56) of plastics that relate to general heat and deformation. The above three temperatures are closely related to each other, and among them, the glass transition temperature (glass transition point) is the temperature at which a resin starts to flow, and the deflection temperature is the temperature at which a specified bending increment is reached under a load (0.45 MPa or 1.80 MPa) at a constant heating rate. The glass transition point is a basic, inherent value of a resin, and is easy to discuss.
[0033] In contrast to the above, the heat distortion temperature used in the present invention is used to examine the limit temperature of deformation under load, and is close to the deflection temperature measured by the official measurement method. However, the load used to measure the deflection temperature is far too heavy and far removed from the practical conditions of the tray. That is, in the case of 0.45 MPa, it is about 4.59 kgf / cm 2 When applied to the practical conditions of a tray, for example, the surface area is 30 x 30 cm 2 This means that 4100kgf parts will be loaded onto the tray, and the parts will be extremely heavy for practical use. For this reason, the heat distortion temperature of the tray made from the PET sheet material targeted by the present invention will be evaluated using our own method, as this is a comparison and examination under a general load during the transportation of the tray and within the expected environmental temperature range. The in-house method used will be explained below.
[0034] First, in consideration of practical use, we assumed a practical comparative study of the temperature at which a tray loaded with parts can withstand deformation when stacked in multiple layers, i.e., heat distortion temperature, and studied a measurement method that allows for relative comparison that can be used for that purpose. The in-house method has the same basic concept as the deflection temperature (heat distortion temperature) standardized by ASTM. In the technical field that is the subject of the present invention, first, for the trays to be used, in consideration of the practical state, we assumed the weight placed on the bottom tray when the trays are stacked, and instead of changing the temperature continuously, we obtained and evaluated the temperature at which the trays can withstand deformation (heat distortion temperature) under conditions of being left stationary at a constant temperature (70°C, 80°C, and 90°C) and at a constant humidity and for a constant time.
[0035] When calculating the heat distortion temperature, the load applied by our company is 3g / cm on the flat surface of the tray. 2 A load of 1000 g was applied evenly, and the tray was left to stand at a specified temperature and humidity for 30 minutes, then returned to room temperature, and changes in the measurement points of the tray (dimensional changes in length, width, and depth) were measured. The evaluation by the above-mentioned in-house method was deemed to pass if the dimensional changes in each part were within 1%. In addition, the specific object of the present invention is to obtain a "humid heat distortion temperature" of 80°C or higher by the above-mentioned in-house method. In addition, in the present invention, essential components in each resin layer of the upper layer, middle layer, and lower layer constituting the PET sheet of the present invention are specified, but additives such as stabilizers, various fillers and various pigments for increasing rigidity, and other resins for improving chemical resistance and imparting surface lubricity, which are added to the molding resin used in vacuum molding, can be used appropriately within the range that does not impair the object of the present invention. In addition, it is acceptable to coat the surface of the PET sheet with paint within the range that does not impair transparency.
[0036] <Resolving issues regarding resistance to heat and humidity distortion temperature> As described above, in order to obtain a heat distortion temperature (80°C or higher) when using a blend (mixed use) of A-PET and PC in a single layer, it is necessary that the mass ratio of PC is 30 to 40% or more. In this case, there is a practical problem that the material cost becomes high. On the other hand, the preferred volume ratio of A-PET / polycarbonate in the intermediate layer defined in the present invention is 98 / 2 to 70 / 30. When PC is expressed in terms of mass ratio based on the specific gravity of PC of 1.20, the upper limit of the ratio of PC is 25, and it is possible to keep the amount of PC used low. Furthermore, since the A-PET part in the resin layer containing a blend of A-PET and PC is incompatible, it corresponds to the phase equivalent to the sea in the sea-island structure and is affected by humidity [see Polymer Literature Collection Vol49 No4, P327 - P334 (1992)]. However, according to the study by the present inventors, when a three-layer structure of PC / A-PET / PC defined in the present invention is used, surprisingly, the influence of humidity is suppressed, and it is confirmed that the heat and humidity distortion temperature of 80°C or higher is achieved. On the other hand, according to the study by the present inventors, it was difficult to sufficiently and stably prevent the influence of humidity in a single layer of a blend of A-PET and PC or a two-layer structure of PC / A-PET. Furthermore, the present inventors confirmed that when the sheet is formed into a three-layer structure of PC / A-PET / PC defined in the present invention, even if the existing mass ratio of PC in the entire layer is less than 30%, it can be sufficiently dealt with, and the heat and humidity distortion temperature can be made good as targeted by the present invention. Therefore, according to the present invention, without causing a problem of a significant cost increase of the product as in the prior art caused by the high material cost of the material applied to vacuum forming, it is realized that a tray with a high heat and humidity distortion temperature can be easily obtained, and the object of the present invention is achieved.
[0037] <Configuration and effect of delaying the time until the crystallization start of the A-PET resin layer> The inventors have further surprisingly found that, in addition to the basic configuration of the present invention described above, when the resin layer of the intermediate layer, which is mainly composed of A-PET, is configured to contain a small amount of polycarbonate, the workability during vacuum molding can be improved in addition to the above-mentioned effects. Specifically, it has been found that the time until the start of crystallization of A-PET, the main component of the intermediate layer, which occurs during vacuum molding, can be delayed (i.e., the delay time can be extended). By extending the delay time, it is possible to suppress the progress of crystallization of A-PET during vacuum molding, and the whitening that occurs in the tray product due to the progress of crystallization can be suppressed, and the transparency of the A-PET material is maintained in the tray obtained by vacuum molding, so that it is possible to obtain excellent products with excellent workability and at the same time stably.
[0038] In the present invention, the temperature condition for the confirmation test on the effect of delaying the time until the start of crystallization was 135°C, taking into consideration the working temperature in vacuum molding of the A-PET sheet and the temperature at which crystallization starts. As a result of the confirmation test on the delay time, it was confirmed that the time until the start of crystallization of A-PET, the main component of the intermediate layer, can be delayed by making the intermediate layer, which is a resin layer mainly composed of A-PET, contain PC and make the volume ratio of A-PET / PC = 98 / 2 to 70 / 30. In other words, it was found that the addition of PC to the intermediate layer mainly composed of A-PET can obtain an effect on the delay time even in a very small amount. This point will be described later.
[0039] The effect of delaying the time until the onset of crystallization accompanied by whitening of A-PET, which was newly discovered by the inventors and obtained by adding a small amount of PC to the intermediate layer mainly composed of A-PET, cannot be explained only by the increase of a few degrees in the glass transition point caused by adding a small amount of PC. The presence of islands in the sea when blended at a ratio of A-PET / PC = 98 / 2 to 70 / 30 may have an effect. Although the reason is unclear, by making the embodiment of the PET sheet of the present invention into a preferred three-layer structure composed of the upper layer mainly composed of PC / intermediate layer mainly composed of A-PET with a small amount of polycarbonate added / lower layer mainly composed of PC, it was found that in addition to obtaining the effect of improving the wet heat distortion temperature, which is the main object of the present invention, the time until the onset of crystallization of A-PET during vacuum molding can be delayed and extended, and the effects of improving workability and maintaining the transparency of the tray obtained by vacuum molding can be stably obtained.
[0040] Next, each material constituting the PET sheet of the present invention will be described. As described above, the PET sheet of the present invention is characterized by having a three-layer structure consisting of an upper layer, an intermediate layer, and a lower layer, which are made of the materials listed below. Each layer constituting the three-layer structure and the materials for forming these layers will be described below.
[0041] <About the middle class> (Main component: A-PET) First, the A-PET, which is the main component constituting the intermediate layer, will be described. As explained above, amorphous A-PET resin is very easy to crystallize when heated, but the degree of crystallization is said to depend on the molecular weight. For example, "Polymer, Vol. 23, No. 258, P673 (1966)" describes the molecular weight dependence of the crystal growth rate of PET, and it is considered that PET in the low molecular weight region can be the starting point of crystallization and can be a factor in promoting the overall crystallization. Therefore, the molecular weight of A-PET can be an important factor. However, according to the study by the present inventors, it was not possible to confirm that the molecular weight of A-PET has an effect on the delay time until crystallization, particularly when the PET sheet that is the subject of the present invention is applied to vacuum molding to manufacture a tray, which is the subject of the present invention.
[0042] In the course of their investigation, the inventors recognized that other index values that are correlated with the molecular weight of A-PET, rather than the molecular weight, could be used as indexes that are correlated with processability, workability, and the like when applied to vacuum molding. They then found that it is effective to use the intrinsic viscosity (IV value), which is correlated with the size of the molecule, as this index value. Since the molecular weight of PET cannot be easily measured, the IV value is a value that is used as a relative guideline by dissolving it in a solvent such as a phenolic solvent and measuring the viscosity. The method for measuring the IV value is described in JIS K7390 (Test method for recycled polyethylene terephthalate (PET) molding material). Specifically, the viscosity of a liquid dissolved in a solvent of phenol / chloroethane = 6 / 4 is measured. The measured value is expressed in units of dL / g. According to the investigations by the inventors, it is preferable that the A-PET, which is the main component constituting the intermediate layer used in the present invention, has an IV value within the range of 0.5 to 1.3, measured using a phenol / 1,1,2,2 tetrachloroethane solvent of 1 / 1. That is, if it is less than 0.5, it is difficult to stabilize the molding conditions, whereas if it exceeds 1.3, the plasticizing viscosity is high, making it difficult to set molding conditions that ensure accurate transcription of the mold dimensions.
[0043] The main structure of A-PET is a high molecular weight polyester produced by condensation polymerization of terephthalic acid and ethylene glycol. As a means of lowering the degree of crystallization or the rate of crystallization of A-PET resin, there is a modified copolymer called PETG or G-PET, which is mainly made of terephthalic acid, with a small amount of isophthalic acid added, or part of the ethylene glycol is replaced with cyclohexanedimethanol. Although such modified resins can be used in the present invention, it should be noted that they are more expensive than unmodified resins and have inferior rigidity compared to A-PET. As examples of A-PET that can be used in the present invention, the properties of commercially available A-PET manufactured by TEIJIN Co., Ltd. and Nanya Plastics Co., Ltd. are shown in Table 1. These A-PETs were used in the examples described below. Of course, the present invention is not limited to these resins.
[0044] TIFF2025016166000001.tif61170
[0045] (Other Ingredients) The intermediate layer constituting the PET sheet of the present invention may be made of the above-mentioned A-PET as a main component, and may be made entirely of A-PET as a material, in addition to additives added appropriately as necessary. It is also preferable that the intermediate layer contains polycarbonate (PC) and has a volume ratio of A-PET / polycarbonate = 98 / 2 to 70 / 30. As described above, according to the study by the present inventors, by making the intermediate layer a configuration in which a small amount of PC is added within the above range, the time until the start of crystallization accompanied by whitening of A-PET, the main component of the intermediate layer, can be delayed when the PET sheet of the present invention is applied to vacuum molding. This means that the time during which good processing can be performed by vacuum molding can be extended, and therefore the workability is excellent. Furthermore, by making the intermediate layer have the above-mentioned configuration, the obtained product is good and maintains transparency. The polycarbonate (PC) material added to A-PET, the main component of the intermediate layer, is not particularly limited, but the same material (material) as that for forming the upper layer and lower layer described later can be preferably used.
[0046] <About the upper and lower layers> (Polycarbonate (PC)) The PET sheet of the present invention has a three-layer structure in which an upper layer and a lower layer containing polycarbonate (PC) are laminated on the front and back of an intermediate layer mainly composed of the above-mentioned A-PET. The PC constituting the upper and lower layers will be described below. PC is a linear or branched polymer obtained by reacting an aromatic dihydroxy compound or a small amount of a polyhydroxy compound with phosgene or a carbonic acid diester. A typical product has a molecular weight of about 15,000 to 30,000 measured at a solution viscosity (25°C) using methylene chloride as a solvent. In the present invention, when selecting PC as a material constituting the upper and lower layers, a suitable range in which the effects of the present invention can be obtained is determined by the melt mass-flow rate value measured as described below, rather than by the molecular weight, and the PC material is selected based on this value.
[0047] As a result of the study by the present inventors, a suitable material for PC, which is the main component of the upper and lower layers constituting the PET sheet of the present invention, is a polycarbonate having a melt mass flow rate (ISO1133) value at 300°C in the range of 3 to 30 (g / 10 min) and a deflection temperature measured by JIS7191 B method of 100°C or more and 150°C or less. The melt flow rate specified above is one of the scales for measuring the fluidity of molten plastics, and the deflection temperature is also called the heat distortion temperature, and is an index of heat resistance index and rigidity (elastic modulus) of a material at high temperatures. Here, the deflection temperature is the temperature at which the deflection becomes constant when the temperature is increased under a load applied to the resin. The deflection is measured by a three-point bending method, and the temperature is gradually increased at 120°C / hour under a constant load (a low load of 0.45 MPa in the present invention), and the temperature is determined as the temperature at which a reference displacement is reached. The deflection temperature allows the heat resistance of materials to be compared relatively, with a larger value indicating a higher resistance to thermal load. According to the inventors' study, for the PC constituting the PET sheet of the present invention, a deflection temperature (0.45 MPa) of less than 100°C results in a low heat distortion temperature, while a deflection temperature of more than 150°C is not preferred because it makes extrusion workability difficult. According to the inventors' study, when selecting a PC material to be used in the present invention, it is more preferred to use one with a deflection temperature range of 120°C or more and 145°C or less.
[0048] Examples of commercially available PC that can be suitably used in the present invention include the products shown in Table 2, all of which are manufactured by Mitsubishi Engineering Plastics Corporation. Of course, the present invention is not limited to these products.
[0049] TIFF2025016166000002.tif77170
[0050] <About the three-layer structure> The PET sheet of the present invention has a three-layer structure consisting of an intermediate layer mainly composed of A-PET, and upper and lower layers containing polycarbonate (PC) laminated on the front and back of the intermediate layer. According to the studies of the present inventors, the total thickness of the laminate having the three-layer structure is preferably about 300 μm to 1200 μm. The ratio of the total thickness of the upper and lower layers to the thickness of the intermediate layer is preferably 10 / 90 to 30 / 70. Therefore, for example, when the total thickness of the laminate is 300 μm, the total thickness of the upper layer and the lower layer is about 30 μm to 90 μm, and the thickness of the intermediate layer is about 210 μm to 270 μm, based on the ratio of the total thickness of the upper layer and the lower layer to the thickness of the intermediate layer. For example, when the total thickness of the laminate is 1200 μm, the total thickness of the upper layer and the lower layer is about 120 μm to 360 μm, and the thickness of the intermediate layer is about 840 μm to 1080 μm. From the above, it is preferable that the thickness of the intermediate layer is about 210 μm to 1080 μm, and the thickness of the upper layer and the lower layer is about 30 μm to 360 μm. The thicknesses of the upper layer and the lower layer may be the same or different from each other, but it is preferable that they are the same thickness in terms of the efficiency of the production of the PET sheet. The term "similar thickness" means that, for example, when an upper layer and a lower layer are laminated on the front and back of an intermediate layer by a method such as extrusion molding, layers having substantially the same thickness are formed.
[0051] <Effects of the present invention> The PET sheet of the present invention has a three-layer structure in which an intermediate layer made mainly of the above-mentioned A-PET is laminated on both sides with an upper layer and a lower layer containing polycarbonate (PC), thereby obtaining the following effects.
[0052] (About delay time) The PET sheet of the present invention has a preferred intermediate layer structure in which a small amount of polycarbonate is added to the main component A-PET, and when applied to vacuum forming, it can stably obtain the following effects that could not be achieved by conventional techniques. Here, the sheet processing method by vacuum forming using the PET sheet of the present invention is a method in which the surface of the sheet is heated with various heat sources, and in a state in which the sheet has not yet reached complete melting but is plasticized, a vacuum is drawn to adhere the sheet to a mold, and a molded product of the required dimensions is obtained. The present invention aims to obtain a transparent tray (i.e., a tray that does not whiten) that retains (maintains) the transparency of the material as a molded product.
[0053] The final objective of the present invention is to obtain a tray of desired quality when a PET sheet made of A-PET is applied to vacuum molding, pressure molding, or press molding. In the case of A-PET, which is the material of the PET sheet of the present invention, there is a problem that the entire sheet crystallizes when heated for an extremely short time, i.e., the material is easily changed to a high softening point. For this reason, there is a tendency to end the evacuation in a state (timing) where plasticization is insufficient. In addition, according to the study by the present inventors, the optimal manufacturing conditions vary greatly depending on the heating method of the molding machine. For example, in the case of a sheet with a thickness of about 1 mm, in the case of one-sided heating, the manufacturing cycle is 20 to 60 seconds / cycle. In contrast, in the case of a method that includes a sheet preheating process and then rapid heating on both sides, it is also possible to mold a tray product in a fast manufacturing cycle of 3 to 5 seconds / cycle.
[0054] In the case of using a sheet having a three-layer structure of PC / A-PET / PC as a forming material and vacuum molding using a one-sided heating method, the temperature of the upper surface of the sheet was 170-180°C, that of the lower surface was 160-165°C, and the manufacturing cycle was 30-32 seconds / cycle. In contrast, in the case of a single-layer sheet of A-PET without a laminated structure examined as a comparative example, the upper surface was 125-140°C, the lower surface was 120-125°C, and the manufacturing cycle was 20-25 seconds / cycle. Details will be described later. On the other hand, it has been reported that the clear start temperature of crystallization of A-PET is around 120°C, the maximum rate region of crystallization is the temperature region of 160-180°C, and it slows down again above that temperature (see Molding Processing Vol.5 No.7 P481 (1983)). As mentioned above, the vacuum forming operation and the crystallization of the A-PET material occur in the same region, so when applying sheets made of A-PET, the timing of forming to obtain a good product becomes very strict. If the optimum state is passed, crystallization will immediately progress, causing whitening and making vacuuming impossible.
[0055] Specifically, if the vacuum is drawn before the above-mentioned optimum state, the resulting tray will be transparent but insufficiently plasticized, and will not be able to adhere to the mold, and the dimensions may not be transferred well. As can be seen from the above, if the plasticized state (uncrystallized state) of the A-PET material can be prolonged, that is, if the time (delay time) until the start of crystallization accompanied by full-scale whitening can be prolonged, the vacuum molding process can be allowed to have more time, and a tray with stable and good mold dimensions can be obtained. For this reason, there has been a demand for improving the delay time when products such as trays are obtained from sheets using A-PET as the material. In addition to the main object of the present invention, which is to realize an improvement in the wet heat distortion temperature, which is a drawback when A-PET is used as a tray material as described below, the present invention also aims to solve the above-mentioned technical problems in order to obtain better effects.
[0056] (Improvement of resistance to heat and humidity distortion temperature) As mentioned above, A-PET trays are used to transport various parts. In recent years, the tray surface has been made conductive and they are often used to transport electronic and electrical parts. The incorporation of these parts into various products has spread to international networks, and transportation between regions and countries has become a daily task. In addition, the electronic and electrical parts to be transported are precision parts, so they must be transported and transported carefully. For this reason, the heat resistance of A-PET trays during transportation has become a bigger problem than in conventional use. Specifically, the resistance to atmospheric temperatures during land transportation in a sealed container and shipping by ship has become an issue.
[0057] Specifically, coupled with the recent warming, the temperature of cargo during transport is getting higher every year. According to measurements of the load temperature during ocean transport 10 years ago, it was reported that the temperature reached about 70°C in a container placed on the deck of a transport ship under the equator. In contrast, the glass transition point of general A-PET is said to be about 70°C, so the above-mentioned harsh environmental conditions during transport overlap with the deformation temperature of the tray. In general, the upper limit of the usage temperature range of A-PET is said to be 60°C, and caution is being called for. However, even though caution is being called for in this way about the usage temperature range, currently, most cases are transported in trays made of A-PET alone, and in recent years, there have been many accidents that are thought to be caused by the trays that store parts not being sufficiently resistant to the ambient temperature.
[0058] On the other hand, deformation of the trays containing various parts during transportation requires re-transportation, which not only delays delivery but may also lead to compensation issues in some cases, so there is a strong demand for improving the heat resistance temperature of A-PET trays, and the main purpose of the present invention is to solve this problem. Here, the higher the heat resistance temperature of the trays, the better, but as mentioned above, in practical use, the material cost is a big problem, so this point needs to be taken into consideration. In practice, it can be determined that the problem of thermal deformation during transportation can be avoided if the heat resistance temperature of the trays is 80°C or higher and 100°C or lower. Furthermore, as mentioned above, the thermal deformation of A-PET trays is greatly affected not only by temperature but also by humidity, so it is necessary to improve the "humid heat deformation temperature" including these factors.
[0059] (Maintaining the characteristics of A-PET material: Transparency) The present invention has as its essential objective the improvement of the above-mentioned wet heat distortion temperature, and as its more preferable objective the improvement of the delay time. However, as a prerequisite for this, the technology is premised on maintaining the excellent characteristics of A-PET material, transparency and rigidity, without impairing them. As for a method for improving the heat resistance while maintaining the transparency of A-PET, the following proposals have been made. For example, Japanese Patent No. 4223520 proposes a method in which an A-PET sheet is uniaxially stretched, then vacuum molded to perform primary heat setting, and then further heated in the same mold to perform secondary heat setting, thereby promoting crystallization and improving heat resistance. However, this method is apparently a complicated process with low productivity, and there is a concern of high product costs, and it is considered difficult to put into practical use. In addition, Japanese Patent No. 6165289 proposes a method for manufacturing a transparent and heat-resistant PET container, or an opaque but highly heat-resistant PET container. However, this technology requires the use of PET resin to which fine organic acid metal salts are previously generated by heat and kneading during the preparation of the master batch, and the reacted master batch is added, so the process is complicated and it is considered difficult to put into practical use. In addition, this technology does not mention the effect of humidity on the obtained container, which is an essential issue of the present invention. As described above, the main technical issue of the present invention is to improve the moisture heat distortion temperature, which is not a problem in the prior art, and the solution of this issue is premised on maintaining the transparency of A-PET.
[0060] (Maintaining the characteristics of A-PET: rigidity) A tray sheet using A-PET material has very high rigidity, and prevents damage to parts delivered in the A-PET tray from external forces. In the present invention, it is assumed that this characteristic of A-PET material is maintained. There are many methods for evaluating the rigidity of resin sheets, but in the present invention, the rigidity is evaluated using the transverse elastic modulus used in material mechanics. The transverse elastic modulus of a sheet made of 100% A-PET is 2800 to 3200 MPa, and the transverse elastic modulus of a sheet made of 100% PC, which is a material used in the present invention, is 2900 to 3200 MPa, and both materials show transverse elastic modulus in almost the same range in terms of rigidity. Therefore, in the present invention, it is determined that rigidity is maintained if the transverse elastic modulus of a sheet made of PC / A-PET / PC or a sheet made of PC / A-PET / PC with a small amount of PC added is within ±5% compared to a sheet made of 100% A-PET. This point will be described later. EXAMPLES
[0061] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0062] [Evaluation test for resistance to heat and humidity distortion temperature] (Measurement of humidity and heat distortion temperature) The tray obtained by applying the PET sheet of the present invention to vacuum forming is described below. First, the raw materials and compounding examples of the tray sheet used to make the tray product and the conditions for producing the tray using the sheet are summarized in Table 3. Among the tray production conditions, the extrusion temperature and roll temperature conditions were the same in all examples. Then, the sheet thickness and the composition ratio of each layer of the laminate were changed, and the sheet take-up speed, the gear pump rotation ratio, the mixer component ratio, etc. were continuously changed to produce a sample sheet using a hanger-type T-die. Then, in consideration of the manufacturing method, the thickness ratio of the A-PET / PC sample taken for measurement, especially the intermediate layer, was measured for the components of the cross section of the sheet using FT-IR.
[0063] TIFF2025016166000003.tif135170
[0064] As mentioned above, there is no official test method for "humid heat distortion temperature resistance", so we established our own test method. Using sheets of various configurations produced under the conditions shown in Table 3, trays were produced by vacuum molding, and the resulting trays were used to measure "humid heat distortion temperature resistance". In this invention, the test was performed using a very simple tray of the following shape. Specifically, a tray was produced with a length of 130 mm, a width of 70 mm, a depth of 25 mm, and an edge of the open part on the top surface with a width of 5 mm. The thickness of the bottom of the tray after molding was about 55% of the thickness of the sheet before molding. For example, when the sheet thickness before molding is 0.8 mm, the thickness of the tray after molding is 0.44 mm. In this way, the molding conditions were set so that the thickness of the tray after molding is almost independent of the thickness of the sheet before the test.
[0065] The tray prepared as described above was placed horizontally in a thermohygrostat, and a 3 g / cm2 concentration was applied to the upper surface of the tray. 2 After applying an even load of 1000 psi to the tray, the tray was left to stand at a specified temperature and humidity for 30 minutes, and then cooled to room temperature. After cooling, the dimensional changes in length, width, and depth were measured. A tray was deemed to have passed the moist heat resistance test if the dimensional changes at all measurement points were within 1%. In the present invention, the specified temperatures were set to 70°C, 80°C, and 90°C, and the specified humidity was set to normal humidity levels of 50% and 90%, respectively. The constant temperature and humidity tester used was LHU-113 (product name) manufactured by Espec Corporation.
[0066] (Preparation of test trays) The production of test trays using each PET sheet was carried out by vacuum forming using a vacuum forming machine. The vacuum forming machine used was a top-heating type HU56 manufactured by Shenzhen Longji Machinery Co., Ltd. Table 4 shows the range of temperatures and heating time conditions on the front and back surfaces of the sheet when vacuum forming was performed using the PET sheet, along with examples of the molding results. Then, the trays (good products, indicated as dimensions acceptable in the table) on which the molding results shown in Table 4 were accurately transferred with the dimensions of "transparent and dimensionally acceptable" were subjected to a measurement test of the humidity heat distortion temperature. The sample numbers used in the tray molding examples shown in Table 4 are the same as the sample numbers shown in Table 5 below, which shows the results of the evaluation test of the humidity heat distortion temperature described later.
[0067] TIFF2025016166000004.tif54170
[0068] As shown in Table 5, sample No. 2 is composed of nearly 80% A-PET by volume. As shown in Table 4, sample No. 2 did not crystallize (whiten) even at the high temperatures (160°C to 180°C) required for plasticization. In contrast, sample No. 23 is a single-layer sheet of A-PET as shown in Table 5, but it was confirmed that a good tray product could only be obtained at low temperatures as shown in Table 4. Also, as shown in Table 5, sample No. 1 was capable of molding a tray with accurately transferred dimensions like sample No. 2, but the conditions were slightly stricter than those of sample No. 2, and it was found that slight localized crystallization occurred.
[0069] As specified in the present invention, when PC is used for the upper and lower layers laminated to the intermediate layer, crystallization accompanied by whitening of the A-PET part, which would normally whiten, was avoided in the 160°C to 165°C range. The reason for this is unclear, but considering samples No. 2 to No. 22, which correspond to preferred embodiments of the present invention shown in Table 5 below, it may be due to the effect of adding PC to the intermediate layer. In addition, the effect may occur in the early stage of crystallization without whitening. The vacuum forming machine used is a top-side heating machine, and the temperature of the lower sheet is heat transferred from the temperature of the upper sheet, so it is thought to be unrelated to the way heat is transferred in the sheet configuration. The fact that crystallization of the A-PET in the intermediate layer was avoided in the temperature range of 160°C to 165°C in the above test can be an effective means of achieving the object of the present invention.
[0070] (Evaluation of Wet Heat Distortion Temperature for Each PET Sheet of Examples and Comparative Examples) Table 5 shows the results of the humidity and heat temperature deformation test conducted on tray products having various configurations based on the PET sheet preparation examples and tray preparation examples performed as described above. The "intermediate layer ratio" in the table is the volume ratio of A-PET / polycarbonate. In preparing the intermediate layer, a predetermined mass ratio was calculated in advance based on the specific gravities of PET and PC listed in (Note) in Tables 1 and 2 so that the three-layer structure of each PET sheet would have the volume ratio shown in Table 5. Samples No. 1 to 22 correspond to examples, and Samples No. 23 and 24 correspond to comparative examples.
[0071] TIFF2025016166000005.tif193170
[0072] The symbols indicating the constituent materials in Table 5 are as follows. Polycarbonate 7026U: Mitsubishi Engineering Plastics Corporation ·7027U: See Table 2 7027BF: Mitsubishi Engineering Plastics Corporation ·E2000: See Table 2 ●Polyethylene terephthalate ·3802:See Table 1 ·TR-BB: See Table 1
[0073] The "pass / fail" shown in Table 5 was evaluated according to the following criteria. ◎: Dimensional change is within 1% and transparent after testing ○: Dimensional change is within 1%, transparent but slightly cloudy after testing ×: Dimensional change of 1% or more (large deformation that cannot be measured)
[0074] As shown in Table 5, the PET sheets having a three-layer structure of PC / A-PET / PC, which are sample Nos. 1 to 22 of the embodiment, passed the moist heat distortion temperature test even under the harsh conditions of a temperature of 90°C and a humidity of 90%. On the other hand, the PET sheets made of A-PET alone, which are sample Nos. 23 and 24 of the comparative example, under conditions of a temperature of 90°C and a humidity of 90%, showed unmeasurable deformation.
[0075] [Determination test of delay time for crystallization of A-PET when making trays] (Exam Overview) This test is to compare the time until the crystallization of A-PET, which is associated with the improvement of workability during molding, begins, accompanied by whitening, when a PET sheet is applied to vacuum molding to produce a tray product. In other words, the work time required to obtain a good tray product with maintained transparency is compared. Here, the upper and lower layers of the PET sheet of the present invention are mainly composed of amorphous resin PC, so that it does not crystallize alone except under special conditions. Therefore, by measuring the delay time of samples of various blend compositions of A-PET and PC in the middle layer of the PET sheet of the present invention, which has a two-kind three-layer structure, it is possible to discuss the merits of improving the work conditions during vacuum molding of the two-kind three-layer sheet. For this reason, a sample of a material composition equivalent to the middle layer was prepared and the delay time was measured.
[0076] (Preparation of samples for delay time measurement) Since this sample corresponds to the intermediate layer, the measurement samples were prepared using an injection machine rather than an extruder. First, blends of various volume ratio compositions with different component ratios of PC added to A-PET were dried at 120°C for 10 hours, and then kneaded in an Ikegai PCM45 twin-screw extruder to produce pellets. When producing the pellets, the mass ratio of the materials used was determined in terms of specific gravity so that the component ratio making up the intermediate layer would be the desired volume ratio. Next, the obtained pellets were dried at 120°C for 10 hours, and then injected into a Toshiba IS-75E-2A injection machine at an injection pressure of 50 kg / cm. 2 Injection plates of 2 mm thickness, 55 mm width and 105 mm length were prepared as samples of various compositions at a mold temperature of 25°C and a cooling time of 40 seconds. Plates of 25 mm x 25 mm were cut out from these injection plates to prepare measurement samples. The obtained measurement samples were transparent. The composition ratio of the constituent materials was confirmed using FTIR of a Nicolet IS5 manufactured by Thermo Fisher Scientific. Specifically, the C=O (1769 cm -1 ) and the peak height of the ester bond of PET, C=O (1717 cm -1 The composition ratio was confirmed from the peak height ratio of
[0077] (Measurement and evaluation of delay time) The transparent plate of the measurement sample obtained as described above was placed on a horizontal hot plate at 135±1°C, and the delay time was the time until the black numbers drawn on the hot plate in advance became difficult to distinguish (transparency was no longer maintained). The hot plate was a CT-3HAT machine manufactured by AS ONE Co., Ltd. If the delay time measured in this way was longer than that of the measurement sample of A-PET alone obtained for comparison by the injector in the same manner as described above, it was deemed to have passed. The results obtained are shown in Table 6.
[0078] [Transparency evaluation test of trays made from PET sheets] (Transparency evaluation test method) Usually, the haze method (JIS7361) is used to test the transparency of resins. The PET sheet of the present invention is intended to be applied to vacuum molding to produce trays for transportation, and the transparency was evaluated as follows due to the special nature of its use. That is, the transparency required in the present invention is the transparency of whether or not the parts delivered to the tray can be seen from above the upper tray in the stack. For this reason, a paper with a line drawn in advance was placed on the bottom of the thickness direction of the sample to evaluate the transparency, and if the line could be seen, the sample passed the test. The lines used in the test were pencil hardness HB, and the interval between the lines was 1 mm.
[0079] The PC material constituting the two-kind three-layer PET sheet defined in the present invention is extremely transparent, as is the A-PET, the main component constituting the intermediate layer. Therefore, the practical viewpoint of this test is to determine whether or not transparency is lost in a blend in which PC is added to the A-PET, the main component of the intermediate layer. Therefore, for the transparency evaluation test, a measurement sample (injection plate) made with the injection machine used in the judgment test of the delay time of crystallization accompanied by whitening of A-PET, as described above, was used. The obtained results are shown in Table 6.
[0080] [Evaluation test of the rigidity of trays made from PET sheets] (Rigidity evaluation test method) When evaluating the rigidity of the polymer alloy of polycarbonate resin (PC) and A-PET constituting the intermediate layer of the PET sheet of the preferred form that is the problem of the present invention, it is possible to apply the tensile modulus of elasticity of JIS K7161. However, the present inventors have determined that this is not suitable from a practical standpoint for the following reasons. In this JIS standard, the rigidity is determined from the slope of the stress / strain curve corresponding to strains of 0.05% and 0.25%, so that the mechanical behavior is in an extremely early stage region. In contrast, in practice, the rigidity of the tray is the deformation and distortion of the tray caused by the stacking of parts delivered to the tray, and in addition, the discussion of the change in the distortion is also in mm units. For this reason, the bending modulus of elasticity of JIS K7171 is also in a very small bending strain region, so it is not appropriate to use it to evaluate the rigidity of the tray that is the problem of the present invention, just like the tensile modulus described above.
[0081] From the above, it is believed that the modulus of transverse elasticity used in material mechanics is the most suitable method for evaluating the rigidity of the tray in this invention. This method is described in "Machinery Practical Handbook" (Published by the Japan Society of Mechanical Engineers in 1956, p. 158). This method finds the modulus of transverse elasticity from the relationship between deflection and external force in a range where the deflection of the material changes significantly, and is calculated using the following formula. Deflection δ and modulus of transverse elasticity K are expressed by the following formulas (1) and (2). δ = (6LF) / [4nb8(h 3 )] Formula (1) K = (6L3F) / [δ16b(h 3 )] Formula (2) Here, L is the length between the supports of the plate, b is the thickness of the plate, h is the width of the plate, n is the number of overlapping plates (n=1 in this test), and F is the external force (N) required for deflection δ, and each dimension is in mm.
[0082] In the evaluation test of the rigidity of the tray performed in the present invention, the transverse elastic modulus measured when the deflection δ was set to 1 mm is shown in Table 6. For the measurement, a measurement sample (injection plate) made by the injection machine used in the judgment test of the crystallization delay time of A-PET described above was used. The obtained results are shown in Table 6.
[0083] A value within ±5% of the modulus of transverse elasticity of the comparative measurement sample made of 100% A-PET was deemed to pass the test in terms of rigidity. For example, as shown in Table 6-1, the rigidity value of the comparative injection plate using PET3802 alone is 3219 (MPa), so in the examples in Tables 6-1 to 6-4 in which PET3802 is used as the main component, a rigidity within the range of 3058 to 3380 (MPa) is deemed to pass. The average modulus of transverse elasticity was determined as half the sum of the modulus of transverse elasticity in the flow direction (MD) and the direction perpendicular to the flow direction (TD) during the production of the injection plate. The test machine used was a Strograph VGS5E manufactured by Toyo Seiki Co., Ltd.
[0084] Table 6 shows the results of the above-mentioned "Test to determine the delay time of crystallization of A-PET when making trays", "Test to evaluate the transparency of trays made from PET sheets", and "Test to evaluate the rigidity of trays made from PET sheets". The "whitened area" in Table 6 indicates the state of the measurement sample after heating when the delay time was determined, as observed visually. The rigidity (transverse elastic modulus) in Table 6 is the value for the measurement sample after heating. As shown in Table 6, it was confirmed that even with a small amount of PC added, around 90 / 5, the working time could be extended by twice as long as the measurement sample containing only A-PET for comparison.
[0085] TIFF2025016166000006.tif86170
[0086] TIFF2025016166000007.tif74170
[0087] TIFF2025016166000008.tif73170
[0088] TIFF2025016166000009.tif65170
[0089] TIFF2025016166000010.tif73170
[0090] TIFF2025016166000011.tif63170
[0091] The stiffness values shown in Tables 6-1 to 6-6 are the modulus of transverse elasticity described above. The modulus of transverse elasticity of 100% PC used in these tables is as follows, and all of them were transparent. 7026U:3127MPa 7027U:3101MPa 7027BF: 2970MPa ·E2000:3120MPa The stiffness showed a tendency for the degree of decrease or increase from the transverse elastic modulus of 100% PC to vary depending on the ratio of the combination with A-PET. However, as shown in Tables 6-1 to 6-6, in all cases, the difference was within the range of ±5%.
[0092] The delay time increases with an increase in PC, but the cloudiness of the sample due to crystallization changes especially in the 100 / 0 to 95 / 5 range and beyond. As shown in Tables 6-1 to 6-6, it was confirmed that the delay time increases with an increase in the amount of PC added compared to when the comparative A-PET is 100%. However, as shown in Tables 6-1 to 6-6, the PC addition does not increase significantly above 20 to 30%, so it is preferable to set this range as the upper limit from an economical point of view. In the 100 / 0 to 95 / 5 range, opaque whitening occurs locally, and there is a tendency for the whitening to spread from that point. In the subsequent range of increasing PC, the entire measurement sample becomes lightly cloudy and tends to darken over time, so there seems to be a qualitative difference in the progress of crystallization depending on the amount of PC added. As shown in Tables 6-1 to 6-6, regardless of the type of material, the delay time did not vary significantly when the PET / PC ratio was 70 / 30 or more, so it was determined that the ratio of PC added to A-PET should preferably be in the range of 2 to 30%. When comparing the brands of A-PET resin, the main component, it was confirmed that TR-BB tended to have a longer delay time than PET3802 when the same amount was added. The reason for this is probably due to the fact that TR-BB is a copolymer. [Industrial Applicability]
[0093] Examples of applications of the present invention include the following. (1) A useful tray with excellent rigidity that can withstand high temperature and humidity environments without deformation and in good condition can be made from a three-layer PET sheet of PC / A-PET / PC. (2) This simple method of adding a small amount of PC to the A-PET that makes up the middle layer delays the onset of crystallization of A-PET that occurs during tray production, improving the molding process and thereby increasing workability. (3) The tray obtained by applying the PET sheet of the present invention does not deform in the harsh environments of high temperature and humidity processes and transportation, and damage to the parts placed in the tray that would otherwise occur due to deformation can be suppressed, so that the practical value of the tray is extremely high.
Claims
1. A PET sheet used for vacuum molding, pressure molding, or press molding, A PET sheet characterized in that it is a laminate having a three-layer structure in which an upper layer is a resin layer containing polycarbonate, an intermediate layer is a resin layer mainly composed of A-PET (amorphous PET), and a lower layer is a resin layer containing polycarbonate.
2. 2. The PET sheet according to claim 1, wherein the intermediate layer contains polycarbonate and has a volume ratio of A-PET / polycarbonate of 98 / 2 to 70 / 30.
3. 3. The PET sheet according to claim 1, wherein the polycarbonate constituting the upper layer and the polycarbonate constituting the lower layer have the same thickness.
4. 4. The PET sheet according to claim 3, wherein a ratio of a total thickness of the upper layer and the lower layer to a thickness of the intermediate layer is from 10 / 90 to 30 / 70.
5. 3. The PET sheet according to claim 1, wherein the thickness of the laminate having a three-layer structure is 300 μm to 1200 μm.
6. 3. The PET sheet according to claim 1, wherein the polycarbonate has a melt mass flow rate (ISO 1133) at 300° C. in the range of 3 to 30 (g / 10 min) and a deflection temperature measured by JIS 7191 B method of 100° C. or higher and 150° C. or lower.
7. The PET sheet according to claim 1 or 2, wherein the A-PET is a reaction product obtained by using a homopolymer or modified copolymer as a raw material, the IV value of which, as measured in a 1 / 1 mixture of phenol and 1,1,2,2-tetrachloroethane, is 0.5 to 1.
3.
8. 3. A tray formed by vacuum molding, pressure molding or press molding, the tray being characterized in that the raw material for the tray is the PET sheet according to claim 1 or 2.
Citation Information
Patent Citations
Method for preventing thermal deflection of heat resistant polyester container
JP1997039105A